2010
DOI: 10.1007/s00340-010-4300-7
|View full text |Cite
|
Sign up to set email alerts
|

Optically stimulated heating using Nd3+ doped NaYF4 colloidal near infrared nanophosphors

Abstract: Although efficient in heat generation, gold nanoparticles dedicated for photostimulated localized hyperthermia treatment (LHT) lack luminescent properties suitable for detection in heterogeneous and autofluorescent tissue. Here, we study and report the use of bifunctional luminescent neodymium (Nd 3+ ) ions doped α-NaYF 4 colloidal nanoparticles as potential nanoheaters suitable for LHT. Up to 35°C (0.8°C/mW@514.5 nm) temperature rise in ∼0.5 ml colloidal 25%Nd 3+ :NaYF 4 solution was achieved in comparison to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 26 publications
1
59
0
Order By: Relevance
“…After the treatment, the sample was centrifuged, washed several times with deionized water, and air-dried at 100 C for 2 h. a-NaYF 4 :Nd 3þ NPs were synthesized via a thermal decomposition method as described in the literature. 37 Briefly, the reaction was carried out in a mixed solvent consisting of oleic acid (OA) and 1-octadecene added to the flask containing previously prepared dried trifluoroacetate precursors. The mixture was stirred for about 40 min under vacuum at temperature slightly above 110 C and then heated to 300 C and stirred under nitrogen for 1 h. After cooling the mixture to room temperature, the nanocrystals were precipitated by a mixture of n-hexane and acetone and collected by centrifugation of the suspension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the treatment, the sample was centrifuged, washed several times with deionized water, and air-dried at 100 C for 2 h. a-NaYF 4 :Nd 3þ NPs were synthesized via a thermal decomposition method as described in the literature. 37 Briefly, the reaction was carried out in a mixed solvent consisting of oleic acid (OA) and 1-octadecene added to the flask containing previously prepared dried trifluoroacetate precursors. The mixture was stirred for about 40 min under vacuum at temperature slightly above 110 C and then heated to 300 C and stirred under nitrogen for 1 h. After cooling the mixture to room temperature, the nanocrystals were precipitated by a mixture of n-hexane and acetone and collected by centrifugation of the suspension.…”
Section: Methodsmentioning
confidence: 99%
“…This work constitutes a comparative study of the three Nd:NPs that have already been used for in vivo imaging purposes along with four other Nd 3þ doped systems (NaYF 4 :Nd 3þ , KYF 4 :Nd 3þ , GdVO 4 :Nd 3þ , and Y 3 Al 5 O 12 :Nd 3þ -hereafter Nd:YAG-) whose synthesis, basic characterization, and potential use as infrared biolabels have been reported and proposed. [37][38][39][40] The relevant role played by host in determining the fluorescent properties of Nd:NPs is discussed and, based on the comparative spectroscopic characterization, the ability of the different systems for in vivo imaging experiments will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Gold has high atomic number which enhances the effect of radio-therapy which is further induced by laser hypothermia. One of the recent developments is the use of colloidal solutions of bifunctional luminescent neodymium (Nd 3+ ) ions doped -NaYF4 colloidal nanoparticles [22]. These particles may be excited in the visible or near infrared range.…”
Section: Different Types Of Nanoparticlesmentioning
confidence: 99%
“…Optimisation at 95 o F was achieved in 25 % Nd 3+ :NaYF4 solution. The work reported in [22] has the potential to develop therapeutic agents which could be deducted by molecular agents. Gold nanoparticles coated with biological agents permeate the tumour cells and localize with endosomes.…”
Section: Different Types Of Nanoparticlesmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28] Few previous works have also reported that certain rare earth doped nano-crystals (RE-NPs) could be also used as PhT-NPs, although this possibility has not been demonstrated yet in biocompatible colloidal solutions. 29 Certain RE-NPs have demonstrated to be highly efficient luminescence probes under excitation with Near Infrared (NIR) radiation within the biological windows. [30][31][32] An additional advantage of RE-NPs is that they can be used for high resolution fluorescence bioimaging by using CW laser sources; much simpler and affordable that the short pulse lasers required for traditional fluorescence probes used in multiphoton fluorescence microscopy.…”
mentioning
confidence: 99%